2002
DOI: 10.1063/1.1482800
|View full text |Cite
|
Sign up to set email alerts
|

Metalorganic vapor-phase epitaxial growth of vertically well-aligned ZnO nanorods

Abstract: We report metalorganic vapor-phase epitaxial growth and structural and photoluminescent characteristics of ZnO nanorods. The nanorods were grown on Al 2 O 3 (00•1) substrates at 400°C without employing any metal catalysts usually needed in other methods. Electron microscopy revealed that nanorods with uniform distributions in their diameters, lengths, and densities were grown vertically from the substrates. The mean diameter of the nanorods is as narrow as 25 nm. In addition, x-ray diffraction measurements cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
708
1
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,145 publications
(735 citation statements)
references
References 18 publications
20
708
1
6
Order By: Relevance
“…Due to the high surface-to-volume ratio provided by the one-dimensional (1D) nanostructure, ZnO nanorod arrays are considered suitable to the application for hybrid photovoltaic devices [4][5][6][7]. In the past few years, ZnO nanorods have been synthesized via various physical and chemical methods including vapor phase synthesis [8][9][10], metalorganic chemical vapor deposition (MOCVD) [11][12][13], and solution-based synthesis [14][15][16][17]. Among these routes, solution-based method has the advantages of simplicity, low costs, low growth temperature, and easy coating of large surfaces Intensive research has been focused on the solution growth process of ZnO nanorods on ITO-coated glass substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high surface-to-volume ratio provided by the one-dimensional (1D) nanostructure, ZnO nanorod arrays are considered suitable to the application for hybrid photovoltaic devices [4][5][6][7]. In the past few years, ZnO nanorods have been synthesized via various physical and chemical methods including vapor phase synthesis [8][9][10], metalorganic chemical vapor deposition (MOCVD) [11][12][13], and solution-based synthesis [14][15][16][17]. Among these routes, solution-based method has the advantages of simplicity, low costs, low growth temperature, and easy coating of large surfaces Intensive research has been focused on the solution growth process of ZnO nanorods on ITO-coated glass substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Among various 1D nanostructural materials, Zinc oxide (ZnO) has generated great interests due to its direct wide band gap of 3.37eV at room temperature, large exciton binding energy of 60meV, and stable physical and chemical properties. Until now, different fabrication methods, such as vapor-phase transport [7][8][9], pulsed laser deposition [10], chemical vapor deposition [11,12] and electrochemical deposition [13], have been widely reported for the preparation of 1-D ZnO nanorods. According to these methods, the complex processes, sophisticated equipment and high temperatures are usually required.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of 1D single-crystalline ZnO nanostructures has been of growing interest owing to their promising application in nanoscale optoelectronic devices. Single-crystalline ZnO nanowires have been synthesized successfully in several groups [16][17][18][19][20]. Wang et al reported the synthesis of oxide nanobelts by simply evaporating the commercial metal oxide powders at high temperatures [3,[19][20].…”
mentioning
confidence: 99%